Prevalence and Correlates of Intestinal Parasites among Patients Admitted to Mirembe National Mental Health Hospital, Dodoma, Tanzania - Nyundo, Azan A. (J Parasitol Res, 2017)
BACKGROUND: Neglected tropical diseases continue to be one of the leading causes of morbidity and mortality in the developing world. Psychiatric patients are among groups at risk for parasitic infection although control and monitoring programs largely overlook this population. This study aimed at determining prevalence and factors associated with intestinal parasitic infection among patients admitted to a psychiatric facility. METHOD: The study followed cross-sectional design; all the residing patients that met the inclusion criteria were included in the survey. Stool samples were collected and examined by direct wet preparation and formol-ether concentration. Data were analyzed with STATA version 12.1; Chi-square test was computed to determine the level of significance at p value < 0.05. RESULTS: Of all 233 patients who returned the stool samples, 29 (12.45%) screened were positive for an intestinal parasite. There was no significant association between parasite carriage and age, sex, or duration of hospital stay. CONCLUSION: The study shows that intestinal parasitic infection is common among patients in a psychiatric facility and highlights that parasitic infections that enter through skin penetration may be a more common mode of transmission than the oral route. Furthermore, the study underscores the need for surveillance and intervention programs to control and manage these infections.